Vision: Running into differences - Psarou, Eleni; Patel, Shivangi; Schölvinck, Marieke (eLife, 2024)
Body movement does not significantly increase neuronal activity in the primary visual cortex of marmosets, in contrast to the effects observed in mice.
Keywords: marmoset; visual cortex; locomotion; electrophysiology; vision